Exposure of Heligmosomoides polygyrus and Trichuris muris to albendazole, albendazole sulfoxide, mebendazole and oxantel pamoate in vitro and in vivo to elucidate the pathway of drug entry into these gastrointestinal nematodes - Cowan, Noemi (Int J Parasitol Drugs Drug Resist, 2017)
Millions of people are treated with anthelmintics to control soil-transmitted helminth infections; yet, drug distribution in the plasma and gastrointestinal tract compartments and the pathway of drug uptake into gastrointestinal nematodes responsible for the pharmacological effect are unknown. We assessed the distribution and uptake of albendazole, albendazole sulfoxide, albendazole sulfone in the hookworm Heligmosomoides polygyrus in vitro and in vivo as well as the distribution and uptake of albendazole, mebendazole, and oxantel pamoate in the whipworm Trichuris muris in vitro and in vivo. Oral and intraperitoneal treatments (100 mg/kg) were studied. Drug quantities in helminths and host compartments (stomach, the contents and mucosa of the small and large intestine, and the plasma) were determined using HPLC-UV/vis and anthelmintic activities were recorded using phenotypic readout. The influence of 1-aminobenzotriazole (ABT), an irreversible and unspecific cytochrome P450 inhibitor, on albendazole disposition in mice harboring H. polygyrus was evaluated. In vivo, albendazole was found in quantities up to 10 nmol per ten H. polygyrus and up to 31 nmol per ten T. muris. ABT did not change the levels of albendazole or its metabolites in the plasma of mice harboring H. polygyrus or in H. polygyrus, whereas drug levels in the gastrointestinal tract of host mice doubled. Mebendazole and oxantel pamoate quantities per ten T. muris were as high as 21 nmol and 34 nmol, respectively. Albendazole revealed a very dynamic distribution and high rate of metabolism, hence, H. polygyrus and T. muris are exposed to albendazole and both metabolites via multiple pathways. Diffusion through the cuticle seems to be the crucial pathway of oxantel pamoate uptake into T. muris, and likely also for mebendazole. No relationship between concentrations measured in helminths and concentrations in plasma, intestinal content and mucosa of mice, or drug efficacy was noted for any of the drugs studied.